Catastrophic flooding, palaeolakes, and late Quaternary drainage reorganization in northern Eurasia. Issue 14 (25th October 2016) - Komatsu, Goro; Baker, Victor R.; Arzhannikov, Sergei G.; Gallagher, Ronnie; Arzhannikova, Anastasia V.; Murana, Alessio; Oguchi, Takashi
ABSTRACT: We review the long history of Russian scientific study of the major late Quaternary palaeodrainages and palaeolakes in northern Eurasia to provide overviews of (1) past research efforts (mainly published in the Russian language) and (2) recent studies that include contributions from those outside of the former Soviet Union region. There are two major groups of catastrophic flooding phenomena and related palaeodrainage and palaeolake systems in this region: (1) those involving large-scale lowland basins and (2) those involving upland intermontane basins. Many of these palaeodrainages and palaeolakes were active during the late Quaternary, though the available age data are inconclusive in regard to more exact timing and synchronicity. These palaeodrainages and palaeolakes in the late Quaternary are strongly linked with climatic change, most notably to ice age. For the megalakes in large-scale basins, spillover events probably occurred because of impoundment by the late Pleistocene Arctic ice sheets. In some cases, gradual transgressions of the megalakes caused by varying climatic conditions could also have contributed to the spillovers. Some of these spillover events may have been catastrophic. Ice-dammed lakes formed when drainage into intermontane basins was impounded by late Pleistocene alpine-type glaciers. The collapses of the glacier dams caused downstream catastrophic flooding, producing a characteristic suite of flood-related landforms. In the Azas Plateau volcanic field, there is evidence for Icelandic-type subglacial flooding.